SN 2023gpw: Exploring the diversity and power sources of hydrogen-rich superluminous supernovae - Kangas, T.; Charalampopoulos, P.; Nagao, T.; Yan, L.; Stritzinger, M.; Schulze, S.; Das, K.; Elias-Rosa, N.; Fremling, C.; Perley, D.; Sollerman, J.; Muller-Bravo, T. E.; et al. (EDP Sciences, 2026)
We present our observations and analysis of SN 2023gpw, a hydrogen-rich superluminous supernova (SLSN II) with broad emission lines in its post-peak spectra. Unlike previously observed SLSNe II, its light curve suggests an abrupt drop during a solar conjunction between similar to 80 and similar to 180 d after the light curve peak, which is possibly analogous to a normal hydrogen-rich supernova (SN). Spectra taken at and before the peak show hydrogen and helium "flash" emission lines attributed to early interaction with a dense confined circumstellar medium (CSM). A well-observed ultraviolet excess appears as these lines disappear, also as a result of CSM interaction. The blackbody photosphere expands roughly at the same velocity throughout the observations, indicating little or no bulk deceleration. This velocity is much higher than what is seen in spectral lines, suggesting asymmetry in the ejecta. The high total radiated energy (greater than or similar to 9 x 10(50) erg) and aforementioned lack of bulk deceleration in SN 2023gpw are difficult to reconcile with a neutrino-driven SN simply combined with efficient conversion from kinetic energy to emission through interaction. This suggests an additional energy source, such as a central engine. While magnetar-powered models qualitatively similar to SN 2023gpw exist, more modeling work is required to determine if they can reproduce the observed properties in combination with early interaction. The required energy might alternatively be provided by accretion onto a black hole created in the collapse of a massive progenitor star.